MATHEMATICAL MODELING OF NORMATIVE SONOGRAPHIC SIZE OF THE UTERUS AND OVARIES IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE DEPENDING ON THE CHARACTERISTICS OF THE BODY STRUCTURE GIRLS ECTOMORPHIC SOMATOTYPES - Ткаченко, М.М.; Прокопенко, С.В.; Черкасова, Л.А. (World of Medicine and Biology, 2016)
Aim of our work – build and carry out the analysis of regression models individual legal sonographic size of the uterus and ovaries in different phases of the menstrual cycle (MC) based on anthropometric characteristics, parameters and indicators somatometric component body weight in practically healthy girls of ectomorphic somatotype. Materials and methods As part of the agreement on scientific cooperation between the Vinnitsa National Medical University named after Pirogov and National Medical University named after Bogomolets from databank of Scientific and Research Center Vinnitsa National Medical University named after Pirogov taken initial sonographic parameters size of uterus and ovaries, anthropometric and somatotypological parameters of 108 healthy urban girls from Podillia aged from 16 to 18 years in different phases of the MC. Ultrasound examination of the ovaries and uterus conducted using devices Voluson 730 Pro (4-10 MHz convex detector) and "Toshiba SSA-220A" (3.75 MHz convex detector) and at 7, 14 and 21 days MC that is for follicular, ovulation and luteal phase. Anthropometric survey of girls conducted by the scheme V. V. Bunak. Somatotypes of girls we determined by the method of J. Carter and B. Heath, component composition and body mass - by the method of J. Matiegka and the American Institute of Nutrition. In licensing package "STATISTICA 6.1" to develop individual sonographic size of the uterus and ovaries, depending on the characteristics of anthropo-somatotypological indicators in ectomorphic girls (n = 20) somatotype in different phases of the MC, was used the method of stepwise regression analysis. Results. Discussions In girls of ectomorphic somatotype: in follicular phase of MC from 13 possible models ecometric parameters of genitals 12 depend on the total complex of anthropo-somatotypological signs of more than 50% (R2 from 0.647 to 0.902); 6 models including the size of the uterus (R2 from 0.647 to 0.902), 5 models - the size of the ovaries (3 for right, R2 = from 0.684 to 0.792, and 2 for the left R2 = 0,772 and 0.782) and ovarian-uterine index (OUI) model (R2 = 0,756); in the phase of ovulation - all 13 models depend on the total complex of anthropo-somatotypological signs of more than 50% (R2 from 0.661 to 0.902); including 6 models size of the uterus (R2 from 0.703 to 0.902), 6 models - the size of the ovaries (3 for right, R2 = from 0.805 to 0.878 and 3 for the left R2 = from 0.661 to 0.669) and the model OUI (R2 = 0,740); in the luteal phase of MC - all 13 models depend on the total complex of anthropo-somatotypological signs of more than 50% (R2 from 0.535 to 0.902); 6 models including the size of the uterus (R2 from 0.535 to 0.902), 6 models - the size of the ovaries (3 for right, R2 = 0.656 to 0.862 from 3 to the left from R2 = 0.565 and 0.743) and OUI model (R2 = 0,746). When analyzing parameters of ecometric built models of genitals in girls eсtomorphic somatotype set: in follicular phase of MC they include encompassing body dimensions - 37.0% (among them 30.0% belong to size of the uterus, and 45.0% - to size of ovary), the diameter of the body - 20.4% (among them 36.4% belong to size of the uterus, and 54.6% - to the size of the ovaries), longitudinal body dimensions - 16.7% (among them 55.6% belong to size of the uterus, and 44.4% - to the size of the ovaries), total body size (weight) - 7.4% (all included in the size of the uterus), width of distal epiphysis of long bones of the extremities (WDE) - 5.6% (among them 66.7% belong to size of the uterus, and 33.3% - to the size of the ovaries), somatotype components - 5.6% (among them 33, 3% belong to size of the uterus, and 66.7% - to the size of the ovaries), age of girls - 3.7% (among them 50.0% belong to size of the uterus and ovaries), thickness of skin and fat folds (TSFF) - 1.9% (all belong to size of the uterus) and component indices of body weight - 1.9% (all belong to size of the uterus); in ovulation phase their composition include encompassing body dimensions - 39.3% (among them 41.7% belong to size of the uterus, and 58.3% - to the size of the ovaries), the diameter of the body - 18.0% (among them 45, 5% belong to size of the uterus, and 54.5% - to the size of the ovaries), age girls - 9.8% (among them 14.3% belong to size of the uterus, and 85.7% - to the size of the ovaries), TSFF - 9.8% (all belong to size of the ovaries), WDE - 8.2% (among them 60.0% belong to size of the uterus, and 40.0% - to the size of the ovaries), longitudinal body dimensions - 6.6% (all belong to size of the uterus), total body size (weight ) - 4.9% (all belong to size of the uterus) and somatotype components - 3.3% (among them 50.0% belong to size of the uterus and ovaries); in the luteal phase of MC its includes encompassing body dimensions - 36.4% (among them 40.0% belong to size of the uterus and ovaries) SHDE - 18.2% (among them 30.0% belong to uterine size, and 60.0% - to the size of the ovaries), the diameter of the body - 16.4% (among them 55.6% belong to size of the uterus, and 44.4% - to the size of the ovaries), age of girls - 9.1% (including 40.0% of which belong to size of the uterus, and 60.0% - to the size of the ovaries), total body size (weight) - 5.5% (all belong to size of the uterus), longitudinal body dimensions - 5.5% (among them 66.7% belong to size of the uterus, and 33.3% - to the size of the ovaries), TSFF - 5.5% (among them 33.3% belong to uterine size and 66.7% - to the size of the ovaries), somatotype components - 1.8% (all belong to size of the uterus) and component indices of body weight - 1.8% (all size of belong to ovaries).